BAL 31 nuclease as a probe in concentrated salt for the B-Z DNA junction. - Kilpatrick, M W (1983)
The BAL 31 nuclease, an extracellular nuclease from A. espejiana, specifically recognizes and cleaves the salt induced conformational junction between B and Z-DNA. Short segments of (dC-dG) left-handed Z-helix, comprising approximately 1% of the total DNA, are specifically detected within two different recombinant plasmids. The BAL 31 enzyme is highly resistant to inactivation by the presence of high concentrations of a variety of electrolytes that stabilize left-handed helices, is active at physiological pH, and can be used to probe both linear and circular DNAs. Additionally, the nuclease cleaves left-handed (dC-dG)n only very poorly, if at all. Thus, the BAL 31 nuclease can be utilized as a probe for helical junctions and consequently for segments of left-handed DNA that might exist within predominantly right-handed naturally occurring genomes.